2020
DOI: 10.1111/tgis.12672
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of versioning methods to improve the information flow in the planning and building processes

Abstract: Version management is a prerequisite for digital information flow between phases in the planning and building processes. Information evolves over time and many parties retrieve information from the various phases. The aim of this article is to evaluate versioning methods, focusing on geodata buildings in the 3D cadastre process. The main attention in the evaluation is on the comprehensive ISO standard Product Lifecycle Support (PLCS). PLCS is evaluated against two simpler versioning methods, the versioning in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Furthermore, none of the tools we are using will be able to natively handle these data. We have previously conducted a study on versioning in this context [57], and found that the versioning capabilities in CityGML 3.0 [38,58] would satisfy the versioning requirements of the (investigated) city applications. Therefore, we made the pragmatic decision that it is most economical to wait to implement versioning in 3CIM in a later version, possibly based on CityGML 3.0.…”
Section: No Versioning In This Version Of 3cimmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, none of the tools we are using will be able to natively handle these data. We have previously conducted a study on versioning in this context [57], and found that the versioning capabilities in CityGML 3.0 [38,58] would satisfy the versioning requirements of the (investigated) city applications. Therefore, we made the pragmatic decision that it is most economical to wait to implement versioning in 3CIM in a later version, possibly based on CityGML 3.0.…”
Section: No Versioning In This Version Of 3cimmentioning
confidence: 99%
“…Both of these limitations could be resolved in a later version of 3CIM, if it is based on CityGML 3.0. This new version of CityGML introduces a new versioning mechanism [57], as well as the possibility to model logical spaces [38].…”
Section: International Standardsmentioning
confidence: 99%
“…The problem highlighted on the additional information is that it requires a substantial restructuring of the technical solution and work processes. In addition, the increasing complexity of the database implementation increases with the number of versioning features included (Eriksson et al, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, the term version often means different instance models resulted from simultaneous, distributed modeling operations [113]. In this paper, variants are instance models representing the same realworld object in a different manner while versions are instance models representing the real-world object at different times in terms of temporal snapshots of the real-world object [99,114]. Different variants/versions are caused by instantiating different schema models (Figure 5) or instantiating one schema model differently (Figure 9).…”
Section: Model-driven Contextual Linkingmentioning
confidence: 99%
“…Another example is checking the consistency of two information models to communicate model modifications. For instance, consistency checks after the handover of building information (e.g., IFC) to a city model (e.g., CityGML) [99] or in the field of railway infrastructure [100]. The application-oriented perspective on information integration based on the described categories corresponds to research in the field of "BIM-GIS Integration".…”
mentioning
confidence: 99%